Exploring physiotherapists’ knowledge and perception of exercise intensity in outpatient stroke rehabilitation: A qualitative study - Félix Nindorera; Bénédicte Jean-Michel; Noémie C. Duclos; Krista L. Best; Stéphane Mandigout; Stéphanie Goncalves (PLoS ONE, 2025)
Objectives To explore physiotherapists’ knowledge and perception of exercise intensity and to identify factors influencing the attainment of recommended exercise intensity during rehabilitation sessions. Methods A qualitative study was conducted using semi-structured, face-to-face interviews with physiotherapists (PTs) who provide stroke rehabilitation within outpatient private settings. Data were audio-recorded, transcribed, and analysed using an inductive content analysis approach. Results Twelve physiotherapists (five women; median age: 44.5 years; median experience: 20 years) who routinely provide stroke rehabilitation participated in the study. Three overarching themes emerged: knowledge about exercise intensity, perception of provided exercise intensity and factors influencing the achievement of recommended intensity. Although 92% of PTs recognized the importance of exercise intensity, only 33% were aware of exercise intensity guidelines. A lack of knowledge regarding exercise intensity assessment, grading, and monitoring was commonly reported. Nearly half (41%) of the PTs reported providing moderate-to-vigorous intensity exercise to stroke survivors. Limiting factors to achieving recommended exercise intensity included patient-related factors (e.g., stroke severity, motivation, cognitive impairments, fatigue), work environment constraints (e.g., limited space), and PT-related challenges (e.g., lack of knowledge, limited contact with doctors). On the other hand, facilitators included high motivation among stroke survivors, large workspace, equipment availability, and the use of group-based training modalities. Conclusion Achieving the recommended exercise intensity in outpatient stroke rehabilitation is influenced by personal, environmental, and PT-related barriers. Multifactorial facilitators, such as improved knowledge, enhanced workspaces, interdisciplinary collaboration, and group-based training approaches, should be considered by stakeholders to ensure the effective implementation of evidence-based stroke rehabilitation practices in private settings. Future research involving PTs with diverse educational backgrounds are needed to strengthen the transferability of these findings.